Pro ASP.NET Extensibility - Krause, Joerg (Apress : Imprint: Apress, 2009)
ASP.NET's model for supporting language extensibility is intriguing to developers everywhere. With support for traditional, statically compiled languages like C# as well as dynamic languages like Python, ASP.NET now has a natural ability to support languages that developers want to work with, not ones they are forced to use. ASP.NET is quickly becoming an attractive place for today's dynamic languages. Pro ASP.NET Extensibility gives readers in-depth insight into the language model within ASP.NET, going beyond the introductory treatment of the topic available elsewhere, providing lots of practical tips and tricks from an experienced developer. Learn about the extensibility and runtime models available with both .NET 3.5 and 4.0, Windows Server 2003 and 2008, and Internet Information Services (IIS) 6.0 and 7.0. The book explains not only how things work, but also why. Using Joerg Krause's experienced advice and sound tricks, you'll be able to go further with your very own language projects and transform your .NET development on your own terms-made possible with ASP.NET's popular extensibility model. Discover how ASP.NET is extensible in .NET 3.5 and 4.0. Look in-depth into the internals of ASP.NET page processing. Customize the behavior of the ASP.NET engine.